Evaluation of Building Vulnerability to Earthquake Using Rapid Visual Screening (RVS) Method - Dwi Pratama, Andhika Ronald; Soetjipto, Jojok Widodo; Krisnamurti, Krisnamurti (Jurnal Teknik Sipil dan Perencanaan, 2021)
Indonesia is one of the countries prone to earthquakes. One of the earthquake disasters that occurred several years ago hit Palu and Donggala on September 28, 2018. It caused severe damage to infrastructure. Therefore, it is necessary to evaluate buildings vulnerable to earthquakes as a form of prevention. One of the buildings in Jember, the dr. Soebandi hospital, experienced cracks in the walls during an earthquake measuring 6.0 on the Richter scale in Nusa Dua Bali on July 16, 2019. This study carried out the risk assessment of the vulnerability of buildings to earthquakes using the Rapid Visual Screening (RVS) method from FEMA P-154. RVS is a method to identify a building that is potentially vulnerable to earthquake hazards based on visual observations from the exterior and interior of the building. The results of the evaluation using the RVS method showed that the dr. Soebandi hospital is categorized as safe and not prone to earthquakes, with a potential vulnerability percentage of 0.0126%. Based on these results, the building does not require special treatment to anticipate earthquakes; however, maintaining the occupants' safety and extending the building's life requires routine maintenance.